PENGARUH KOMPOSISI DEPOSIT NaCl/Na 2 SO TERHADAP KOROSI TEMPERATUR TINGGI BAJA AISI 4130 YANG DILAPISI ALUMINIUM 4 - Saputra, Yudhistyra; Badaruddin, Mohammad; Zulhanif, . (Jurnal Ilmiah Teknik Mesin FEMA, 2014)
Steel AISI 4130 is a combination steelof 1,0 Cr-0,25 Mo-Fe that mostly used for the component heat axchanger and pipe steam   boiler. However in a high temperature and contain of corrosive gas like klor and sulfur,the endurance of the corrosion of steel AISI 4130 declines. It is important to do a research for increasing the endurance of the corrosion of the steel AISI 4130 with heated Al layered in the surface of steel AISI 4130 Al layered and oxidized in temperature 750°C during periods 1-49 jam. The calibration of the corrosion is done with the variation of deposit NaCl/Na The finding of the research shows that the existence of deposit NaCl/Na2 SO in the steel Al layered brings a large influence oxidation kinetics steel, it is proven through the largest value of parabolic constants of the steel AISI 4130 with Al layered with the comparison of deposit  NaCl/Na4(gr):30/70 is 6,89 × 10-9 g2 cm–4 s–1. Whereas the value of parabolic constants with the comparison of deposit (gr): 100/0 is 2,71 × 10 -9 g2 cm–4 s–1, 50/50 is 6,15 × 10 -9  g2 cm–4 s–12 SO24SO4 , 70/30 is 2,97 × 10 g2 cm –4 s–1 and 0/100 is around 2,60 × 10 -9  g 2 cm –4s–1. The destruction of the protective layer Al in the aluminide layer is caused by the existence of klor dan sulfur from the deposit NaCl/Na2SO4 thattriggersthe growthofiron-rich ovide (FeO).Keywords : steel AISI 4130, Al hot-dip, deposit NaCl, deposit Na2SO4 , Al2O3, iron oxide.